Urethral Strictures after Transurethral Surgery: Treatment and Histological Issues - S. V. Kotov; R. I. Guspanov; A. G. Yusufov; M. K. Semenov; E. Kh. Abdulkhalygov; M. M. Iritsyan; I. I. Survillo (Креативная хирургия и онкология)
Introduction. The development of upper and lower urinary endoscopic surgery has brought about an increase in the number of urethral strictures after transurethral procedures.Material and methods. A retrospective analysis was performed involving the treatment results of 72 patients with urethral strictures after transurethral surgery in 2011-2016. All the patients underwent standard examination, including US, residual urine analysis, uroflowmetry, retrograde and micturating urethrography, IPSS and QoL questioning and general clinical tests.Results and discussion. The median of observation comprised 28 months. Bulbous urethra appeared to be the most frequent localisation of urethral strictures (87.5 %). The median stricture length was 2 cm with the mean maximum urine flow rate equal to 5.9 ± 2.7 mL/s. The median IPSS score counted 25 points. The type and number of surgical procedures were as follows: internal optic urethrotonomy (29), anastomotic urethroplasty (18), single-stage skin flap urethroplasty (3), single-stage urethroplasty using buccal mucosa graft (17), multiple-stage urethroplasty using buccal mucosa graft (1), meatotomy (1), single-stage navicular fossa urethroplasty using buccal mucosa graft (1). Internal optic urethrotonomy was to be effective in 52 % cases, while other surgical procedures showed 89 % effectiveness. The pathomorpho-logic studies revealed severe inflammation without signs of stroma fibrosis within urethral strictures.Conclusion. Transurethral endoscopic procedures appear to be the main causative factor (in 54 % cases) for iatrogenic urethral strictures.